Evaluation for additional work of waterproofing on the retaining wall and capping beam - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the evaluation for additional work of waterproofing on the retaining wall and capping beam of Brac University new campus development project .